Caracterização química e da atividade biológica de metabólitos especializados presentes em extratos do tubérculo do cará-moela (Dioscorea bulbifera): aplicações potenciais em processos biotecnológicos - Stadniki, Jéssica (2019)
Dioscorea bulbifera is an unconventional food plant (UFPs), popularly known as gizzard, has a great nutritional power and countless are the reports of its biological potential. In order to evaluate the biotechnological properties present in the gizzard tuber, extracts and, from them, the chemical characterization, analyzes of antioxidant, antimicrobial and antitumor potential were obtained (DB-C extract cloroformic, DB-A: ethyl acetate extract, DB-N: Extract n-butanolic and DB-W: Aqueous extract) from the ethanol extract 75% (DB: E) it was possible to identify the DB-W extract as the one that obtained the best yield. Spectra of the analysis Infrared with Fourier Transform (IV-TF) allowed the observation of bands characteristic of hydroxyls, signals suggestive of aromatic compounds and the presence of carbonyl. These IV-TF absorptions are indicative of phenolic compounds. For the analysis of total phenolic compounds (CFT) the extract with the best yield was the DB-A, and for the antioxidant analyzes through the radicals ABTS and DPPH the DB-E, for FRAP the extract DB-W. The responses obtained in the antimicrobial analysis, by means of disk diffusion technique, demonstrate antimicrobial activity for Staphylococcus aureus and Escherichia coli microorganisms. By means of the broth microdilution method, the DB-E extract obtained a response against S. aureus (5,000 ug ml-1), DB-C against S. aureus and Candida. albicans (10,000 ug ml-1), for the DB-N extract showed activity against all tested microorganisms (10,000 and 5,000 ug ml-1), for DB-A against S. aureus (10,000 ug ml -1), E. coli and C. albicans (5,000 ug ml-1). The antimicrobial action was characterized as bacteriostatic and fungistatic. When analyzing the antitumor activity, the ability to inhibit the proliferation of the Raji, K562, Jurkat and HL60 cell lines by extracts DB-A, DB-C, DB-N was observed through the MTT (tetrazolium) method, where it is observed the latter with the best result. The data obtained in this research point to the existence of compounds of scientific, microbiological and industrial importance in the tuber of D. bulbifera, serving as the basis for future research that may help in the elucidation of the mechanism of action of the substances present.